1998
DOI: 10.1042/bj3310649
|View full text |Cite
|
Sign up to set email alerts
|

Purification of catalytic domain of rat spleen p72syk kinase and its phosphorylation and activation by protein kinase C

Abstract: The catalytic domain of p72(syk) kinase (CDp72(syk)) was purified from a 30000 g particulate fraction of rat spleen. The purification procedure employed sequential chromatography on columns of DEAE-Sephacel and Superdex-200, and elution from HA-Ultrogel by chloride. The analysis of the final CDp72(syk) preparation by SDS/PAGE revealed a major silver-stained 40 kDa protein. The kinase was identified by covalent modification of its ATP-binding site with [14C]5'-fluorosulphonylbenzoyladenosine and by immunoblotti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
(58 reference statements)
0
11
1
Order By: Relevance
“…This is a novel finding, but because of the nonselectivity of BIM among the PKC isoforms it is not possible at this stage to assess whether Btk is specifically regulated by associated PKC. Precedence for the activation of a tyrosine kinase by PKC-mediated phosphorylation has been set by the demonstration that PKC␦ phosphorylates and activates the kinase c-Abl in vitro (39), PKC activates Fyn (40), and PKC␣, ␤1, ␤2, and ␥ are upstream of Syk (41). In other cell types, PKC isoforms have been shown to phosphorylate Btk, leading to an inhibition of Btk activity (13), and therefore our data are in contrast with these reports.…”
Section: Discussioncontrasting
confidence: 55%
“…This is a novel finding, but because of the nonselectivity of BIM among the PKC isoforms it is not possible at this stage to assess whether Btk is specifically regulated by associated PKC. Precedence for the activation of a tyrosine kinase by PKC-mediated phosphorylation has been set by the demonstration that PKC␦ phosphorylates and activates the kinase c-Abl in vitro (39), PKC activates Fyn (40), and PKC␣, ␤1, ␤2, and ␥ are upstream of Syk (41). In other cell types, PKC isoforms have been shown to phosphorylate Btk, leading to an inhibition of Btk activity (13), and therefore our data are in contrast with these reports.…”
Section: Discussioncontrasting
confidence: 55%
“…The PKC-mediated serine phosphorylation of the catalytic subunit of Syk has been previously shown to increase its in vitro kinase activity (62), although this activity has not been confirmed in recent studies with human platelets (49). We show that the PKCmediated serine phosphorylation of Syk is necessary for its MSU crystal-induced tyrosine phosphorylation because both Gö6976 and silencing PKC␣ diminish it.…”
Section: Discussionmentioning
confidence: 67%
“…In contrast, Borowski et al . reported that the 40 kDa catalytic domain of Syk, a partially degradated product, purified from rat spleen was phosphorylated and activated by PKC in vitro (Borowski et al 1998). Therefore, it is possible that in intact cells, an unknown modification by some factor(s) enabled Syk to receive direct phosphorylation and activation by PKC.…”
Section: Discussionmentioning
confidence: 99%